Improvement of regional development using current and strategic territorial management mechanisms - Borbasova, Z.N.; Nessipbayev, R.E.; Ulakov, S.N.; Ulakov, N.S. (BUKETOV BUSINESS REVIEW, 2020)
Object: The successful development of the regions requires certainty and the presence of consolidating ideas about the future. These are important needs of business and society, which are satisfied through the mechanism of territorial socio-economic planning. This article discusses the concept of strategic management, describes the differences between strategic and current management on the example of management of sectors of the social block. The essence of the management of the territorial economy of the region, as well as issues of the implementation of life support and social services of the population, improvement of the territorial economy as a whole was investigated. Methods: The following methods were used during the research: empirical, analytical, synthetic and comparative logical ones. Findings: Therefore, the main form of territorial management is the combination of current and strategic management within the governing body. The implementation of this approach requires a very careful attitude to the construction of the internal structure of the management body, taking into account the peculiarities of the organization of different types of management. Let's try to give a more detailed description of the main approaches to building management structures focused on combining current and strategic management. Conclusions: When forming a strategic planning mechanism, one should proceed from the need to respect the interests of all participants in the development of the territory: government, business, and the public. But the driving force is always the government: it not only realizes its interest, but also creates conditions for the effective functioning of enterprises, improving the investment climate of the territory, provides equal competitive opportunities for all partners in the region. A well-developed strategic plan is the basis for implementing more detailed plans for each year.